A new possibility for ensuring clean air in farm buildings - Póti, Péter; Vertséné Zándoki, Rita; Kosztolányiné Szentléleki, Andrea; Baschán, Árpád; Pajor, Ferenc (Animal welfare, Ethology and Housing Systems (AWETH), 2023)
Stall air may contain various contaminants (gases, dust, microorganisms, viruses) that are harmful for animals and workers. Smallest dust particles (<2,5 μm) can enter even lower parts of the respiratory system, carrying pathogens on their surfaces. Proper production level can be expected only in a healthy stock, and air quality has singnficant effect on health and welfare status of animals. Contagious diseases like African swine fever and bird flue regularly bring farmers into hard situations. Stall climate also affects health and comfort of farm workers. Aim of the study was to introduce an innovative technology in air cleansing of indoor livestock housing technologies. In MESP (mikroelectrostatic precipitation) technology, insulated filters with electrostatic maze are applied that remove dust, fungi, black, fume, and inactivate bacteria and viruses. This technology has not been applied in farm buildings yet. MESP technology avoids waste production: filters are ready to be used again after washing, without loss of efficiency, with a lifetime of approximately 10 years. Osone production is negligable. There is neither electric arc formation, nor danger of electric schock. No risk of microbial contamination takes place. Its energy demand is low. MESP can be applied within wide ranges of temperature and air humidity conditions (-15 ℃ - 50 ℃, even 100% humidity). In tests, efficiency results for elimination of viruses and bacteria were 96,84 - 99,99% and >99,99%, respectively. MESP technology can be an ideal solution for defence against contagious diseases in indoor housig systems.